Konsentrasi Katalis dan Suhu Optimum pada Reaksi Esterifikasi menggunakan Katalis Zeolit Alam Aktif (ZAH) dalam Pembuatan Biodiesel dari Minyak Jelantah - Kartika, Dwi; Widyaningsih, Senny (Jurnal Natur Indonesia, 2012)
Transesterification of waste cooking oil into biodiesel using KOH catalyst with and without esterification process usingactivated natural zeolite (ZAH) catalyst has been carried out. Activation of the zeolite was done by refluxing with HCl 6Mfor 30 min, followed calcining and oxydized at 500oC for 2 hours, consecutively. The transesterification without esterificationprocess were done using KOH catalyst 1% (w/w) from oil and methanol weight and oil/methanol molar ratio 1:6 at 60oC. Theesterification reaction was also done using ZAH catalyst then continued by transesterification using KOH catalyst inmethanol media. In order to study the effect of ZAH catalyst concentration at constant temperature, the catalysts werevaried, i.e. 0, 1, 2, and 3% (w/w). To investigate the effect of temperature, the experiments were done at various temperaturefrom 30, 45, 60, and 70oC at constant catalyst concentration. The conversion of biodiesel was determined by 1H-NMRspectrometer and physical properties of biodiesel were determined using ASTM standard methods. The results showedthat the transesterification using KOH catalyst without esterification produced biodiesel conversion of 53.29%. The optimumcondition of biodiesel synthesis via esterification process were reached at 60oC and concentration of ZAH catalyst of2% (w/w), that could give biodiesel conversion = 100.00%. The physical properties were conformed with biodiesel ASTM2003b and Directorate General of Oil and Gas 2006 specification.